Penegakan Hukum Pidana Terhadap Penjual Minuman Beralkohol Jenis Sopi di Maluku Tengah - Laga, Alif Farhan; Lewerissa, Yanti Amelia; Tuhumury, Carolina (PATTIMURA Law Study Review, 2024)
ABSTRACT: All types of alcoholic beverages, including liquor, have been around for a long time. Private consumption of liquor is considered unlawful. Law enforcers have difficulty eradicating the habit of consuming alcohol which has become embedded in society. Regional Regulation No.02 of 2015 in Maluku, especially in Salahutu District, regulates the control and distribution of alcoholic beverages. If someone does not have a business license to sell liquor, they will lose out on funds. In Maluku itself, many people sell liquor in the form of sopi illegally or without an Alcoholic Drinks Trading Business License (SIUP-MB). The aims of this research are (1) to examine and analyze law enforcement for providers or sellers of sopi type alcoholic drinks in Central Maluku, and (2) to study and analyze the concept of criminal law enforcement against providers or sellers of sopi type alcoholic drinks in Central Maluku. In this research, the author uses empirical juridical law. For resource persons, involving residents in Liang village who often consume sopi alcoholic drinks, traditional leaders, Liang village government staff, and Babinkamtibmas. Data collection techniques in research are divided into 2, namely, literature study and field study. Based on the research results, it can be seen that the penalties governing alcoholic beverages are very weak so that they do not impose criminal sanctions on sellers of illegal alcoholic beverages, only goods (sopi) are confiscated as evidence. A draft law on alcoholic beverages should be created to resolve all problems related to alcoholic beverages, including sectoral regulations, non-uniform regional regulations, and law enforcement.